2018
DOI: 10.3390/ijms19072014
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Leucine-Rich Repeat Flightless-Interacting Protein-1 Improves Healing of Acute Wounds through Its Effects on Proliferation Inflammation and Collagen Deposition

Abstract: Wound healing is an increasing clinical problem involving substantial morbidity, mortality, and rising health care costs. Leucine-rich repeat flightless-interacting protein-1 (LRRFIP-1) regulates toll-like receptor (TLR)-mediated inflammation, suggesting a potential role in the healing of wounds. We sought to determine the role of LRRFIP-1 in wound repair and whether the exogenous addition of recombinant LRRFIP-1 (rLRRFIP-1) affected healing responses. Using a model of full-thickness incisional acute wounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Addition of recombinant LRRFIP1 (rLRRFIP1) to human keratinocytes and fibroblasts in vitro, increases proliferation and metabolic activity (Kopecki et al, 2018b), similar to the effect of reducing Flii expression by siRNA knockdown and indicating that competition between Flii and LRRFIP1 upon the β-catenindependent proliferation may be a primary pathway affected. In vivo, the intradermal delivery of rLRRFIP1 to the margins of mouse incisional wounds exhibit similar effects to reduced Flii activity, with accelerated re-epithelialisation and smaller more contracted wounds by day 7 post-injury (Kopecki et al, 2018b). Interestingly, increased numbers of proliferating cells were only observed in the neoepidermis and not in the dermal wound fibroblasts (Kopecki et al, 2018b), whereas mice with reduced Flii exhibit increased proliferation in both (Cowin et al, 2007), suggesting that LRRFIP1 alone is not sufficient to prevent Flii inhibition of proliferation in wound fibroblasts.…”
Section: Flii As a Negative Regulator Of Wound Healingmentioning
confidence: 85%
See 2 more Smart Citations
“…Addition of recombinant LRRFIP1 (rLRRFIP1) to human keratinocytes and fibroblasts in vitro, increases proliferation and metabolic activity (Kopecki et al, 2018b), similar to the effect of reducing Flii expression by siRNA knockdown and indicating that competition between Flii and LRRFIP1 upon the β-catenindependent proliferation may be a primary pathway affected. In vivo, the intradermal delivery of rLRRFIP1 to the margins of mouse incisional wounds exhibit similar effects to reduced Flii activity, with accelerated re-epithelialisation and smaller more contracted wounds by day 7 post-injury (Kopecki et al, 2018b). Interestingly, increased numbers of proliferating cells were only observed in the neoepidermis and not in the dermal wound fibroblasts (Kopecki et al, 2018b), whereas mice with reduced Flii exhibit increased proliferation in both (Cowin et al, 2007), suggesting that LRRFIP1 alone is not sufficient to prevent Flii inhibition of proliferation in wound fibroblasts.…”
Section: Flii As a Negative Regulator Of Wound Healingmentioning
confidence: 85%
“…Wound healing investigations into the effect of LRRFIP1, with which Flii competes to influence the regulation of a number of pathways crucial to wound repair, may shed some light upon the specific Flii interactions that dictate the overall effect of Flii in a broader in vivo context. Kopecki et al (2018b) report that LRRFIP1 is predominantly expressed by keratinocytes in unwounded skin, but upon wounding its expression is upregulated in both keratinocytes and fibroblasts. Addition of recombinant LRRFIP1 (rLRRFIP1) to human keratinocytes and fibroblasts in vitro, increases proliferation and metabolic activity (Kopecki et al, 2018b), similar to the effect of reducing Flii expression by siRNA knockdown and indicating that competition between Flii and LRRFIP1 upon the β-catenindependent proliferation may be a primary pathway affected.…”
Section: Flii As a Negative Regulator Of Wound Healingmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study revealed that LRRFIP1/GCF2 plays an important role in the repair processes of acute wounds [66]. In the response to incisional skin wounding in mice, LRRFIP1/GCF2 was significantly up-regulated in fibroblasts and keratinocytes in the dermis and epidermis of the skin.…”
Section: Implications For Human Diseasementioning
confidence: 99%
“…The interest in natural products as potential wound agents is evidenced through three articles that investigated healing responses to honey [4], deoxyshikonin [5], and anthocyanins extacted from Oryza sativa L [6]. Understanding cytoskeletal interactions in keratinocytes and fibroblasts [7] as well as neutrophil proteome signatures [8] also provide important new information that may inform researchers with the development of new therapeutic approaches to improve healing responses. Altering TLR [9] and inflammasome signaling [10] provide further important insights into healing responses.…”
mentioning
confidence: 99%